2017
DOI: 10.1007/s11060-017-2530-9
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke after radiation therapy for pituitary adenomas: a systematic review

Abstract: strokes. Included studies described different radiation techniques and regimens and different lengths of follow-up. In conclusion, complications of cerebral ischemia after radiotherapy for pituitary adenoma are infrequently reported. Moreover, after correction for several confounders, no significant difference in ischemic stroke rate between irradiated and non-irradiated patients could be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Radiation can cause apoptosis and subsequent endothelial loss. Local inflammatory response and upregulation of hypoxia-related genes can lead to vascular injury, atherosclerosis and thromboembolism [ 26 ]. These data emphasise the potential issues pertaining to normal tissue receiving excess radiation and the need for our analyses here.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation can cause apoptosis and subsequent endothelial loss. Local inflammatory response and upregulation of hypoxia-related genes can lead to vascular injury, atherosclerosis and thromboembolism [ 26 ]. These data emphasise the potential issues pertaining to normal tissue receiving excess radiation and the need for our analyses here.…”
Section: Discussionmentioning
confidence: 99%
“…Temozolomide is an orally administered alkylating drug that is well-tolerated by glioma patients; however, its myelotoxic effect can be severe and long-lasting. A prospective study showed that grade III-IV lymphopenia (absolute lymphocyte count <500 cells/mm 3 ) and CD4 lymphopenia (CD4 lymphocyte count <200 cells/mm 3 ) occurred in 40% of patients with high-grade astrocytoma ( 3 ), and another study reported that lymphopenia remained throughout a 48-week observation period ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significant rate of cerebrovascular accidents (CVA) and mortality after CRT have been of great concern: CVA 4% at 5 years and up to 21% at 20 years was noted in 334 patients with various pituitary tumours irradiated with 3-field CRT in 1962 -1986 (19). More recently, other studies showed lower rates, varying between 0 -11.6% (20,21). Increased mortality has been also reported in patients with acromegaly or NFPAs treated with CRT: 1.6 -4.1 times higher compared to general population (22)(23)(24)(25)(26)(27), mainly due to cerebrovascular disease.…”
Section: Radiation Techniquesmentioning
confidence: 96%
“…Local tumour control has been achieved in 83 -100% of patients (median 94%), at a median followup (mFU) of 47.3 months (21.7 -95) using a median marginal dose of 16 Gy. Notably, doses delivered to the tumour margin are lower for NFPA (10 -20 Gy) than for secreting adenomas (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (36). In a large study (512 patients), progression-free survival was 95% and 85% at 5, respectively 10 years FU (46).…”
Section: Nonfunctioning Pituitary Adenomasmentioning
confidence: 99%